2011
DOI: 10.1074/jbc.m110.204859
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin Mediates Anti-inflammatory Effects of Nicotine in Lipopolysaccharide-stimulated Macrophages

Abstract: Nicotine inhibits the release of TNF-␣ from macrophage through activation of STAT3. Tristetraprolin (TTP) is known to destabilize pro-inflammatory transcripts containing AU-rich elements (ARE) in 3-untranslated region (3-UTR). Here we show that in LPS-stimulated human macrophages the anti-inflammatory action of nicotine is mediated by TTP. Nicotine induced activation of STAT3 enhanced STAT3 binding to the TTP promoter, increased TTP promoter activity, and increased TTP expression resulting in the suppression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…E: One representative EMSA out of at least n = 3 independent experiments using oligonucleotides being complementary to IL-6-RE 6 of the LPA promoter (left panel) and using oligonucleotides in which the specifi c STAT3 binding sequence (CTGGGA) of IL-6-RE 6 is mutated (right panel). The STAT3 supershift antibody used specifi cally blocks the DNA binding domain resulting in disappearance of the STAT3 shift [also see ( 36 )]. In summary, the data obtained in the present study suggest that IL-6 blockade by monoclonal antibodies might be a promising future therapeutic approach to treat elevated serum Lp(a) concentrations and to reduced CVD risk in affected patients and might therefore be a convenient alternative to lipid apheresis.…”
Section: Tcz Regulates Lpa Promoter Activity Via An Re At ؊ 46 To ؊ 40mentioning
confidence: 75%
“…E: One representative EMSA out of at least n = 3 independent experiments using oligonucleotides being complementary to IL-6-RE 6 of the LPA promoter (left panel) and using oligonucleotides in which the specifi c STAT3 binding sequence (CTGGGA) of IL-6-RE 6 is mutated (right panel). The STAT3 supershift antibody used specifi cally blocks the DNA binding domain resulting in disappearance of the STAT3 shift [also see ( 36 )]. In summary, the data obtained in the present study suggest that IL-6 blockade by monoclonal antibodies might be a promising future therapeutic approach to treat elevated serum Lp(a) concentrations and to reduced CVD risk in affected patients and might therefore be a convenient alternative to lipid apheresis.…”
Section: Tcz Regulates Lpa Promoter Activity Via An Re At ؊ 46 To ؊ 40mentioning
confidence: 75%
“…Upregulation of TTP is a new method of cancer prevention (Griseri et al, 2011;Kim et al, 2012). TTP expression can be regulated through NF-kB, p38MAPK, STATs and other signaling pathways Joe et al, 2011). Resveratrol has been confirmed to have effective actions on these signaling pathways (Bhardwaj et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that TTP expression can be regulated through NF-kB, p38MAPK, STATs, and other signaling pathways Joe et al, 2011). Resveratrol has been confirmed to play effective roles in the same signaling pathways (Bhardwaj et al, 2007).…”
Section: Effects Of Resveratrol On Ttp Expression and Downstream Pathmentioning
confidence: 99%
See 1 more Smart Citation
“…However, LPS stimulation does not enhance the TTP-mediated degradation of ARE-containing mRNA because it also activates p38 MAPK, which can phosphorylate and inactivate TTP (Chrestensen et al, 2004;Stoecklin et al, 2004). Stimulation with IFN-γ (Sauer et al, 2006), IL-10 (Schaljo et al, 2009) or nicotine (Joe et al, 2011) has been reported to induce TTP expression but not p38 MAPK activity and thus these agents increase the induction of mRNA decay by TTP. IFN-γ has been reported to increase both the level and the activity of TTP and enhance the TTPmediated degradation of IL-23 mRNA in macrophages (Qian et al, 2011).…”
Section: Discussionmentioning
confidence: 99%